Transformasi Praktik PAUD melalui Pelatihan Pembelajaran Kreatif Berpusat Pada Anak Berbasis Bahan Lokal di Manggarai Timur - Fransiskus De Gomes; Maria Angkur; Ignasius Febryanto R. Bora (FKIP Universitas Mataram, 2026)
This community engagement program aimed to enhance the capacity of early childhood education (ECE) teachers and administrators to implement creative, play-based, and child-centered learning practices. The program was conducted in partnership with the Gugah Nurani Indonesia (GNI) Foundation, Borong Community Development Program (CDP), on 22–23 April 2026 in Borong, East Manggarai Regency, East Nusa Tenggara, Indonesia. A participatory-reflective training approach was employed, encompassing needs assessment, pre-test, instructional sessions, hands-on workshops on developing educational play materials (EPM) using locally available resources, preparation of learning modules, development of child development assessment instruments, post-test, and follow-up reflection. The program involved 40 ECE teachers and administrators as participants. The findings demonstrated a significant shift in participants' capacity from merely understanding theoretical concepts to being able to design more practical and contextually relevant learning activities. Participants developed a more consistent understanding of the teacher's role as a facilitator, developmentally and interest-based lesson planning, play-based learning, differentiated instruction, and the use of locally available materials as learning resources. Practical experience in developing seven types of educational play materials and designing learning modules further strengthened participants' implementation skills. The program recommends continuous mentoring, systematic classroom implementation monitoring, and the strengthening of teacher learning communities to institutionalize sustainable improvements in teaching practices within early childhood education settings.